Temporal trends in guideline-recommended medical therapy after an acute heart failure decompensation event: an observational analysis from Generator Heart Failure DataMart - Antonio Gasbarrini; Giuseppe Patti; Filippo Crea; Giovanni Scambia; Domenico D'Amario; Vincenzo Valentini; Gianluigi Savarese; Alfredo Cesario; Jacopo Lenkowicz; Stefano Patarnello; Renzo Laborante; Agni Delvinioti; et al. (BMJ Open)
Objectives To evaluate the trend of prescription of the four foundational therapies, and their impact on 30-day urgent re-admissions and all-cause death in patients with heart failure and reduced ejection fraction (HFrEF) following an acute decompensation event.Design Retrospective.Setting One tertiary referral centre.Participants 999 consecutively patients admitted with a primary diagnosis of HFrEF between January 2020 and June 2023 were identified through a validated, high‐performance technology infrastructure based on artificial intelligence. The entire cohort was divided into three time periods based on two time points: September 2021 (ie, the release of the latest European guidelines) and January 2022 (ie, reimbursement for sodium-glucose cotransporter 2 (SGLT2) inhibitors).Primary and secondary outcome measures Trends and predictors of the prescription of each of the four foundational therapies and of the composite of all-cause death and rehospitalisation for urgent causes at 30 days.Results Among the 999 included patients, β-blockers were prescribed in 93% of patients, ACE inhibitor (ACEi)/angiotensin receptor blocker (ARB)/angiotensin–neprilysin receptor inhibitor (ARNi) in 73%, mineralocorticoid receptor antagonist in 30% and SGLT2 inhibitors in 18%. Over time, an increase in the prescription rate occurred only for SGLT2 inhibitors (3% vs 10% vs 32%, p<0.001), whereas the rate of the composite of all-cause death and rehospitalisation for urgent causes at 30 days remained stable (9.9% vs 10.3% vs 8.4%; p=ns). In multivariate analysis, the use of ACEi/ARB/ARNi was associated with a lower risk of 30-day all-cause death and urgent rehospitalisation (adjusted OR 0.38; 95% CI 0.24 to 0.59; p<0.01). Conversely, the prescription of furosemide at discharge (adjusted OR 2.25; 95% CI 95% 1.29 to 3.94; p<0.01) and a previous genitourinary infection (adjusted OR 4.02; 95% CI 1.67 to 9.68; p<0.01) were associated with higher risk of 30-day all-cause death and urgent rehospitalisation.Conclusions In our study, early adoption of guideline-recommended medical therapy is still limited, with a significant rise in SGLT2i prescriptions after January 2022 and a lower risk of the composite of all-cause death and urgent readmissions at 30 days restricted to the use of ACEi/ARB/ARNi.